Concept of a regional silver economy illustrated with the example of Lubusz province - Cupiał, Brygida; Sobolewska-Poniedziałek, Ewa (Managerial Economics, 2014)
Demographic trends in developed countries require focus on the problem of aging populations. These trends are directly related to structural changes within the economy. Modifications of economic models imply a need for the creation of a new regional development concept. An example of such a concept is the silver-economy strategy implemented at the regional level. This article attempts to identify the existing potential and the main barriers to the introduction of the silver-economy concept in the region. Investigations will be carried out by a case study of Lubusz Province.